2023
DOI: 10.1038/s43587-023-00442-w
|View full text |Cite
|
Sign up to set email alerts
|

Removal of senescent cells reduces the viral load and attenuates pulmonary and systemic inflammation in SARS-CoV-2-infected, aged hamsters

Abstract: Older age is one of the strongest risk factors for severe COVID-19. In this study, we determined whether age-associated cellular senescence contributes to the severity of experimental COVID-19. Aged golden hamsters accumulate senescent cells in the lungs, and the senolytic drug ABT-263, a BCL-2 inhibitor, depletes these cells at baseline and during SARS-CoV-2 infection. Relative to young hamsters, aged hamsters had a greater viral load during the acute phase of infection and displayed higher levels of sequelae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…as indicated. No statistical methods were used to predetermine sample size, but our sample sizes are similar to those reported in previous publications 19 , 43 . Data distribution was assumed to be normal, but this was not formally tested.…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…as indicated. No statistical methods were used to predetermine sample size, but our sample sizes are similar to those reported in previous publications 19 , 43 . Data distribution was assumed to be normal, but this was not formally tested.…”
Section: Methodsmentioning
confidence: 64%
“…Given the positive survival and improved clinical performance outcomes induced by senolytic treatment, a phenomenon partially explained by reduction in lung senescence (Extended Data Fig. 6c ) and pathology as previously shown 19 , 43 , we investigated whether the oral administration of senolytics would impact the histological architecture and proinflammatory makeup of brains from infected mice. To this end we first tested the impact of senolytics on brain viral RNA levels.…”
Section: Resultsmentioning
confidence: 97%
“…Quantitative RT‐PCR was performed exactly as described in (Delval et al, 2023 ). The murine primers used were as follows: p16 (5′‐GCTCTGGCTTTCGTGAACATGT‐3′, 5′‐TTGAGCAGAAGAGCTGCTACGT‐3′ and ( bcl2 ) (5′‐TCATGTGTGTGGAGAGCGTCA‐3′, 5′‐GATCCAGGTGTGCAGATGCC‐3′) and ( Gapdh ) (5′‐GCAAAGTGGAGATTGTTGCC‐3′, 5′‐ GCCTTGACTGTGCCGTTGA‐3′).…”
Section: Methodsmentioning
confidence: 99%
“…This approach has shown beneficial results in models of lung fibrosis [ 72 ]. Recently, it has been shown that navitoclax decreases viral load, systemic inflammation and SASP markers in a model of COVID-19 in aged hamsters, in line with its senolytic activity [ 73 ]. Other pathways can be blocked using kinase inhibitors.…”
Section: Therapeutic Modulation Of Senescence: Senotherapeuticsmentioning
confidence: 99%